Strategi Indonesia dalam Memajukan Pendidikan Perdamaian sebagai Negara Multikultur di Kawasan Asia Tenggara - Fitri Angelia Hartati Sinambela; Herlina Juni Risma Saragih; Bayu Setiawan; Pujo Widodo; Achmed Sukendro (CV. AFDIFAL MAJU BERKAH, 2025)
A country with so many ethnicities and cultures can be likened to a double-edged sword. This is a very interesting discussion and a concern for many people. This ethnic and cultural wealth can provide beauty, diversity, and harmony if the existing differences are maintained and well-regulated. However, this can also cause problems if there is intolerance and discrimination against an ethnic or cultural group. The most undesirable scenario is when these differences cause divisions in society. This study employs qualitative methods with a descriptive-analytical approach to explore Indonesia's strategies for promoting peace education as a multicultural country in Southeast Asia. Through holistic literature studies and inductive analysis, the research identifies key strategies such as integrating peace education into formal and non-formal systems, fostering collaboration through the Pentahelix model involving academics, businesses, communities, government, and media, and embedding peace values into education curricula. The findings highlight Indonesia's challenges as a multicultural nation with peace vulnerabilities that make conflict difficult to eliminate. The research emphasizes the need to bridge the gap between the ideal goals of peace and the realities of societal conditions. By strengthening peace education, the Indonesian government can address the root causes of disunity and foster harmony. Drawing on the fourth precept of Pancasila, which underscores Indonesia’s commitment to lasting peace and social justice, the study concludes that unity in diversity can be realized through effective education strategies. Initiatives such as the